SYNTHESIS OF DIHYDROPYRIMIDINONE DERIVATIVES AND CYTOTOXIC ACTIVITY TEST AGAINST T47D CANCER CELLS - Hakimah, Wafiq Kholifatul; Fauzi, Ahmad; Ramadhan, Muhammad Reza; Maulina, Fariha Mufidah (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Dihydropyrimidinone (DHPM) derivatives are heterocyclic compounds known for a variety of biological activities including anticancer properties. The Mitsunobu reaction was used in this study to synthesize a new DHPM derivative, ethyl 4-(4-isopropoxy-3,5-dimethylphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate (compound B2), and assess its cytotoxic activity against T47D breast cancer cells. Compound B2 was synthesized from ethyl 4-(4-hydroxy-3,5-dimethylphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydropyrimidine-5-carboxylate (compound M1) using multicomponent reactions (MCR) and the Mitsunobu reaction with isopropyl alcohol as the pronucleophile. Compound B2 was characterized using melting point test, FTIR and LC-MS spectroscopy, which confirmed its structure, functional groups, and molecular weight of 334.13 g/mol. MTT assay was used to evaluate cytotoxic activity. Compound B2 had an IC50 value of 205.71 µg/mL, indicating weak cytotoxicity, whereas doxorubicin had an IC50 value of 3.33 µg/mL. Despite the low cytotoxicity of compound B2, this synthesis sheds light on the development of DHPM derivatives with potential anticancer properties. The results showed that the Mitsunobu reaction is useful for modifying DHPM derivatives and highlights the need for further optimization to improve cytotoxic potency. Keywords: Dihydropyrimidinone, Mitsunobu, Cytotoxicity, T47D